Consumer purchasing behaviour of emotional design in e-commerce - Okur, P.; Aslina Baharum; Ismail, R.; Nazlan, N.; Nur Shahida Ab Fatah; Noor, N.A.M. (World Academy of Research in Science and Engineering, 2020)
When we touched about consumer purchasing behaviour through emotional design, we refer to the three significant attributes; emotion, reasoning, and perception. Then, when we explain further about the emotional design, we are about to touch on the three levels of design; visceral, behavioural, and reflective, respectively. Designing something means designing the emotion and thus, create a vivid and symbolic image of high artistic value. The concept of emotional design is applicable to e-Commerce, an area that is booming nowadays as a result of the significant competition of technology. The findings in this research can be used as a reference in developing an impactful website which will trigger the purchase on the Internet. © 2020, World Academy of Research in Science and Engineering. All rights reserved.